Risk Management in Air Cargo Delivery: Addressing with the House of Risk Framework - Sari, Mustika; Riffat, Muhammad; Nasution, Nursery Alfaridi; Octaviani, Reni Dian (Universitas Mercu Buana, 2025)
Objective: The purpose of this study was to identify the root reasons of delayed products delivery and to create risk-reduction plans for logistics service providers that use air transportation.Methodology: The House of Risk (HOR) approach was utilized, which entailed in-depth interviews and questionnaires filled out by people who were knowledgeable about the problem.Findings: Twelve separate risk events were found, and eighteen risk agents were shown to be involved in these delays. Nine of them were identified as priority risk agents, indicating that they were the main reasons for the delays. In order to limit the hazards identified, the study developed eight preventive strategies that were carefully sequenced to address these difficulties. The study's conclusions are meant to help the business put the suggested mitigation plans into practice. These strategies specifically seek to lower or limit the possibility of delays when carrying air cargo. By putting these strategies into practice, the company may improve the dependability and efficiency of its logistics processes, guaranteeing the timely delivery of goods.Conclusion: The ultimate goal of the research is to provide the organization with practical and effective strategies to reduce or eliminate the probability of disruptions in their logistical operations, particularly concerning aviation cargo shipments bound to Papua. By implementing the recommended preventive measures, the company is expected to increase the dependability and efficacy of their logistics operations, which is the anticipated result of this research. Through the implementation of this strategic approach, the company can effectively bolster customer satisfaction, sustain a competitive advantage within the logistics sector, and ensure punctual deliveries.